A Study of Physician Behaviour and Preference towards Marketing Services Offered by Pharmaceutical Industry to Influence Physician's Perception Behaviour - Parihar, Shubhendra S. (Indian Journal of Marketing, 2010)
Indian pharmaceutical industry is growing at a steady growth rate of 8-9%. The Indian pharmaceutical industry can be divided into the organized and unorganized sector. Around 260 companies are in the organized sector which accounts for 90% share of the Indian pharma market and 20000 pharma companies contribute to rest 10% of the industry. Indian companies either came with off patented drugs or combination of two or more drugs in one pill. A competition between the organized and unorganized sector pushed all big players towards the chronic segment whereas the 'me to drugs' segment was either dominated by the unorganized sector or by the generic brands. Due to increase in competition both domestic and international, most of the pharmaceutical companies focused their efforts to strengthen their relationship with their customers. This trend continued and companies started sharing their profits with their customers. Now the customer for pharmaceutical industry, the doctor, is playing a dual role of shareholder and stakeholder. This shift of customer behavior is now governed by pharmaceutical companies with customer relationship management. Now all companies are having a separate department to identify and cater to the needs and wants of physicians to develop a base of satisfied and loyal customers. Customers are having a lot of offers from different companies which always shakes their loyalty. Sometimes, they give their commitment to support two or three companies for the same product/brand and are unable to fulfill the desired return expected by the company. Many of the surveys have revealed that a satisfied customer does not mean a loyal one. A customer can be satisfied but may not be loyal. Before analyzing the physician's behavior, we must aware of the set of factors which may influence the prescription behavior. There are three basic factors which may influence the prescription behavior of a physician independently or collectively.